Who Is Immersion for?: A Critical Analysis of French Immersion Policies - Kunnas, Marika (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2023)
Elitism has been an issue in Canadian French immersion since its inception. This study examines how two racially diverse Ontarian school boards and Ontario French immersion policy, curricula, and other related documents construct and support an elite student within the immersion program. The elite student who emerged from immersion documents is a White, middle-class, English, established resident, mirroring the current demographics of the program. A middle-class bias emerged within the documents due to an assumed wealth, and lack of financial assistance, transportation and promotional materials. The program locations themselves favoured the middle-class. The curricula demonstrated a Eurocentric focus and colonial lens. In the documents of this study, it was assumed that parents had functional knowledge of English and French. Program entry-points favoured established residents over newcomers. Given its evident elitism, there has been a shift toward inclusion, particularly for students with special education needs and English language learners. However, this inclusion has yet to be critically enacted.